Immediate loading of implants installed in a healed alveolar bony ridge or immediately after tooth extraction: an experimental study in dogs - Mainetti, Tomaso; Lang, Niklaus P.; Bengazi, Franco; Sbricoli, Luca; Cantero, Luis Soto; Botticelli, Daniele [UNESP] (Wiley-Blackwell, 2015)
ObjectiveTo compare the sequential healing at immediately loaded implants installed in a healed alveolar bony ridge or immediately after tooth extraction.Material and methodsIn the mandible of 12 dogs, the second premolars were extracted. After 3months, the mesial roots of the third premolars were endodontically treated and the distal roots extracted. Implants were placed immediately into the extraction sockets (test) and in the second premolar region (control). Crowns were applied at the second and third maxillary premolars, and healing abutments of appropriate length were applied at both implants placed in the mandible and adapted to allow occlusal contacts with the crowns in the maxilla. The time of surgery and time of sacrifices were planned in such a way to obtain biopsies representing the healing after 1 and 2weeks and 1 and 3months. Ground sections were prepared for histological analyses.ResultsAt the control sites, a resorption of the buccal bone of 1mm was found after 1week and remained stable thereafter. At the test sites, the resorption was 0.4mm at 1-week period and further loss was observed after 1month. The height of the peri-implant soft tissue was 3.8mm both at test and control sites. Higher values of mineralized bone-to-implant contact and bone density were seen at the controls compared with the test sites. The differences, however, were not statistically significant.ConclusionsDifferent patterns of sequential early healing were found at implants installed in healed alveolar bone or in alveolar sockets immediately after tooth extractions. However, three months after implant installation, no statistically significant differences were found for the hard- and soft-tissue dimensions.
Keywords: Animal study; Extraction sockets; Histology; Histometry; Immediate loading; IPIES; Type I; Type III; Type IV; Wound healing